2016
DOI: 10.1002/bjs.10173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the first 5 years of a national abdominal aortic aneurysm screening programme

Abstract: The processes in the NHS AAA Screening Programme are effective in detecting and treating men with AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 27 publications
3
62
1
3
Order By: Relevance
“…Based on the observed ratio of men to women (52 per cent women and 48 per cent men) among siblings identified for targeted screening 10 , the cohorts were simulated as a single cohort consisting of both men and women, with proportionately weighted data on mortality and disease prevalence. Attendance (86 per cent) after invitation to screening for siblings 28 was similar to that for men invited to the MASS (80 per cent) 25 , as well as the reported contemporary attendance in the Swedish AAA Screening Programme (84 per cent) 3 and the National Health Service AAA Screening Programme (NAAASP) in England (78 per cent) 1 .…”
Section: Model Assumptionssupporting
confidence: 53%
“…Based on the observed ratio of men to women (52 per cent women and 48 per cent men) among siblings identified for targeted screening 10 , the cohorts were simulated as a single cohort consisting of both men and women, with proportionately weighted data on mortality and disease prevalence. Attendance (86 per cent) after invitation to screening for siblings 28 was similar to that for men invited to the MASS (80 per cent) 25 , as well as the reported contemporary attendance in the Swedish AAA Screening Programme (84 per cent) 3 and the National Health Service AAA Screening Programme (NAAASP) in England (78 per cent) 1 .…”
Section: Model Assumptionssupporting
confidence: 53%
“…It is drummed into rural Australians that they are responsible for their health, so many may have had previous investigations where their AAA will have been diagnosed already. This seems different from the UK and Swedish populations, 5,6 where the background level of investigation appears lower and the rate of undetected disease higher. Screening programs have more to offer populations such as these.…”
contrasting
confidence: 63%
“…3·96 to 31·99; P < 0·001). Similarly, Ulug and co‐workers36 demonstrated that turn‐down rates were higher in women than men (34 versus 19 per cent; OR 2·27, 1·21 to 4·23), compared with 9·2 per cent within the first 5 years of the NHS Abdominal Aortic Aneurysm Screening Programme (men only)37.…”
Section: Discussionmentioning
confidence: 95%